The Use of Youtube Movie Clips in Teaching Listening: Lecturer Practice and Students’ Opinions - Bariqotul Hidayah (Edulitics (Education, Literature, and Linguistics) Journal, 2022)
The use of YouTube in language teaching is no longer considered a new idea. In this study, the researcher investigated the use of YouTube movie clips in teaching listening from a student’s response, specifically in English education class. The study aims at portraying and describing the nature of how the lecturer applies YouTube movie clips in teaching listening classes for university students. The data were collected from the lecturer through observation, interviews, and field notes. A total of 26 English Department students in the Extensive Listening class were chosen as the participants of the study. The result of this study shows the students’ motivation improved by the feedback from their answer and their score. Their participation can be seen when the lecturer gave them feedback on their mistakes in spelling, pronunciation, vocabulary meaning, and content comprehension. The findings also show that there are a lot of ways that can be applied in language teaching by adopting media. Listening could be measured by the response answer to the writing or speaking skill of the students. Authentic material is used to make the relevant material for students’ listening improvement. It is suggested that the lecturer can implement various techniques or media in their language class.